2022
DOI: 10.1039/d2an00010e
|View full text |Cite
|
Sign up to set email alerts
|

Isomeric separation of permethylated glycans by extra-long reversed-phase liquid chromatography (RPLC)-MS/MS

Abstract: Glycosylation is known as a critical biological process that can largely affect the properties and the functions of proteins. Glycan isomers have been shown to be involved in a variety...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 68 publications
(95 reference statements)
0
10
0
Order By: Relevance
“…Fragmentation differences as well as the advantages of using a quadrupole-orbitrap instrument for permethylated Nglycan analysis, were highlighted. While most of the fragment ions shown in this work are b-and y-ions, permethylated Nglycans can undergo multiple cross-ring fragmentations with metal adducts such as lithium, as shown by Kurz et al 55 For our future study, we believe that PRM-based analysis in conjunction with the permethylated glycan isomeric separation technique, such as a mesoporous graphitized carbon column 53 or extra-long C18 column 56 may produce more detailed characterization of glycan isomers without the use of…”
Section: ■ Conclusionmentioning
confidence: 67%
“…Fragmentation differences as well as the advantages of using a quadrupole-orbitrap instrument for permethylated Nglycan analysis, were highlighted. While most of the fragment ions shown in this work are b-and y-ions, permethylated Nglycans can undergo multiple cross-ring fragmentations with metal adducts such as lithium, as shown by Kurz et al 55 For our future study, we believe that PRM-based analysis in conjunction with the permethylated glycan isomeric separation technique, such as a mesoporous graphitized carbon column 53 or extra-long C18 column 56 may produce more detailed characterization of glycan isomers without the use of…”
Section: ■ Conclusionmentioning
confidence: 67%
“…Two previously developed in-house strategies capable of separating an important number of isomeric N -glycans were used to complete the isomeric N -glycan profile of low-abundant serum glycoproteins in MCI samples. The MGC-LC-MS that uses a home-made 10 mm mesoporous graphitized carbon (MGC) column [ 30 ] and the C18(50 cm)-LC-MS that takes advantage of the path length to increase the interactions between analytes and the stationary phase were both used and resulted in isomeric separation [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Later, it was increased to 9% in 3 min and kept constant for 17 min. Finally, it was decreased to 20% in 3 min and maintained to equilibrate the column [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1–4 A glycan is a chain-like molecule of glucose, galactose and other monosaccharide molecules formed in a specific sequence. 5–7 They, as bioinformational molecules, not only determine the functions and metabolic pathways of glycoproteins, but are also involved in almost all life processes of cellular biology. 8–10 It has been identified that the aberrant alterations of N -glycans including increased branching, sialylation and fucosylation can induce various diseases and even accelerate cancer progression.…”
Section: Introductionmentioning
confidence: 99%